IDENTIFIKASI RUANG HUNIAN SEBAGAI UPAYA MENDUKUNG RUMAH PRODUKTIF DI KAMPUNG TENUN IKAT ROTE NDAO - Rhodys Ndoen (JMARS: Jurnal Mosaik Arsitektur, 2022)
The community weaving activities in the Rote Ndao Ikat Weaving Village have been passed down for a long time and have become a specialty of the Rote Ndao community. Ikat weaving is a livelihood as well as improving the economic welfare of the residents of each productive house in Rote Ndao Ikat Weaving Village. Placement of residential space as a workplace through the process of making traditional woven fabrics, limited residential space is a problem in itself, how do actors maximize the available space for their productive activities. The purpose of this study is to identify the activities of residential spaces in order to obtain information about the condition of residential spaces and the activities in them. This research is the result of the exploration of several residential spaces as productive houses in Rote Ndao Tenun Ikat Village. The research method uses descriptive qualitative research methods that are objective data collection including field physical data. The results of the study show that efforts to support productive homes have limited space. Productive activities at the same time as domestic activities greatly affect the efficiency of the function of space. The use of public areas is 62.5%, based on the approach (SKKNI, 2015) The layout design, floor, separation wall & ceiling and ventilation openings in each productive house have not taken into account the technical aspects of the building and the comfort of the craft workers. The average value of natural lighting on the terrace is 174 lux, the living room is 35.5 lux so that the intensity of lighting is still lacking as a productive work space.